Enhancement of quality and stability of dried papaya by pectin-based coatings as air-drying pretreatment - Canizares, Diego [UNESP]; Mauro, Maria Aparecida [UNESP] (Springer, 2015)
Edible coatings have rarely been studied as a pretreatment for air-drying process. Hydrocolloid-based coatings possess good barrier properties to gases, are soluble in water, and can incorporate additives such as ascorbic acid. The aim of the present study was to improve the physical and nutritional characteristics of dehydrated fruits and vegetables by edible coating application. For this, the drying kinetics and the vitamin C and color retention in papaya (Carica papaya L.) with and without edible coatings were evaluated. Color and vitamin C were analyzed after 3, 9, and 30 days of storage. Papaya slices were immersed in a 2 % pectin solution (w/w) or in a 2 % pectin solution with vitamin C (1 % w/w). The pectin coating was gelled by immersion in calcium lactate solution (2.8 % w/w). The pectin-coated and non-coated slices were air-dried at temperatures of 60 and 70 A degrees C. Vitamin C, color, and water content were analyzed in fresh papaya and in coated papaya before and after drying and during storage. All drying experiments were repeated four times. Analysis of variance was applied to the experimental data to identify differences at a 5 % significance level. The drying kinetics of coated and non-coated samples were very similar, only changing with temperature. Even though the highest vitamin C retention has been found in pectin-coated samples during drying at 60 A degrees C and during 30 days of storage, considerable levels of vitamin C were obtained in samples with pectin + vitamin C coating, after drying and storage. Sensory analysis presented positive results for encouraging the use of dried pectin + vitamin C-coated papaya commercially.
Keywords: Edible coating; Papaya; Vitamin C; Color; Drying kinetics; Pectin; Mass effective diffusion; Sensory analysis